Performance of the combination of decarbonisation policy instruments and implications for carbon neutrality in China - Lin Fu; Can Wang (Advances in Climate Change Research, 2022)
Decarbonisation is a complex systemic issue that involves multiple market failures. Thus, the integrated application of multiple policy instruments is required. This study used the fuzzy-set qualitative comparative analysis (fsQCA) method to explore the causality relationship between decarbonisation policies with reference to the Intergovernmental Panel on Climate Change (IPCC) and the decoupling elasticity of Tapio from a configuration perspective. We found that taxation and regulation are the critical drivers of decoupling, while information and public goods and services are ancillary. Three decoupled policy mixes were tabled, each focusing on a) taxation, b) taxation and economic instruments, and c) trading system and regulations. In contrast, the execution of information and voluntary instruments, as well as the non-implementation of the tax, are essential to non-decoupling. Three combinations that are negative for decoupling were also introduced: a) trade and economic incentives, b) trade, information and voluntary instruments, and c) information, public goods and services, and voluntary instruments. The most valuable policy mix for China is the implementation of taxes, trade, economic and regulations with the provision of auxiliary decarbonised information and public goods and services. The following processes are involved: a) integrate regulations with economic policies for more flexibility; b) introduce the carbon tax and a tax rebate policy to complement the carbon market policy based on research into the feasibility and cost-effectiveness; c) provide information and public services mainly on the consumption side; and d) recommend voluntary policies for innovative practices. On the basis of more cases and a configuration perspective, this study offers various policy mixes that are conducive or not to decoupling and suggestions for optimising China’s decarbonisation policy. We also offered a way to measure the intensity of the decarbonisation policy with respect to the carbon emission structure of sectors.